Ácido oleanônico isolado de Lippia lupulina (Verbenaceae) apresenta potentes atividades leishmanicida e tripanocida - Funari, Cristiano S. [UNESP]; de Almeida, Letícia [UNESP]; Passalacqua, Thais G. [UNESP]; Martinez, Isabel [UNESP]; Ambrósio, Daniela L. [UNESP]; Cicarelli, Regina Maria B. [UNESP]; Silva, Dulce Helena S. [UNESP]; Graminha, Márcia A. S. [UNESP] (FapUNIFESP (SciELO), 2016)
Leishmaniasis and Chagas disease affect millions of people in tropical and subtropical regions. Drugs used currently to treat such diseases often present undesirable side effects and low efficiency. The aim of this work was to identify extracts and isolated compounds from the genus Lippia with leishmanicidal and trypanocidal activity. Fifteen extracts from different plant parts of Lippia species with partially known chemical compositions, four partition fractions, six compounds and a mixture of four interconverting flavanones previously isolated from Lippia salviaefolia and Lippia lupulina were assayed in vitro towards epimastigote forms of Trypanosoma cruzi and promastigote forms of Leishmania amazonensis. The root extract of L. lupulina had potent activity against T. cruzi and L. amazonensis (IC50 of 20.0 and 54.5 μg mL–1, respectively). The triterpenoid oleanonic acid showed the strongest activity against these protozoans (IC50 of 18.5 and 29.9 μM, respectively). Our results indicate that Lippia plants and their derivatives deserve further investigation in the search for new antiprotozoal drugs, particularly for the treatment of leishmaniasis and Chagas disease.
Oleanonic acid from lippia lupulina (Verbenaceae) shows strong in vitro antileishmanial and antitrypanosomal activity
Keywords: Flavonoids; Leishmanicidal; T. cruzi; Triterpenoids; Trypanocidal